(untitled) (Journal of Medical & Health Sciences Review, 2025)
Objective: This study aimed to use the sonographic markers in the early detection of renal dysfunction in diabetic adults. Study design: The study design was cross sectional in nature. Place and duration of study: The study was conducted at Allied Hospital Faisalabad. Duration of study was 4 months from November 2024 to February 2025. Material and methods: The current study comprised a sample of 250 persons. All diabetic adults (aged18-90) all BMI categories and both genders were consenting before participation, experienced ultrasonography collected their demographic, anthropometric data and blood samples collection. The data was presented as mean and standard deviation (mean ±SD). One-way analysis of variance (ANOVA) was used to calculate the statistical analysis, and the Pearson correlation coefficient was computed for bivariate associations. The statistical significance was established at the 5% (p<0.05) level using the SPSS version 27. Results: The results showed that male participants had higher serum creatinine and eGFR levels with increasing BMI. Serum creatinine ranged from 0.876±0.341 mg/dL in males with BMI <18.5 kg/m² to 1.325±0.677 mg/dL in those with BMI >30 kg/m², with an overall mean of 0.997±0.503 mg/dL (p=0.113). eGFR increased from 77.257±11.959 mL/min/1.73 m² to 101.125±16.762 mL/min/1.73 m², with a significant p-value of 0.001. In females, serum creatinine ranged from 0.790±0.310 mg/dL in the <18.5 BMI group to 1.097±1.004 mg/dL in the >30 BMI group, with a mean of 0.963±0.798 mg/dL (p=0.014). eGFR ranged from 62.200±10.464 mL/min/1.73 m² to 84.595±13.180 mL/min/1.73 m², with a significant p-value of <0.001. Conclusions: Sonographic variables have demonstrated great promise in the early identification of renal impairment in persons with diabetes. Before symptoms manifest or laboratory data change dramatically, early alterations in kidney size, cortical echogenicity, and resistive indices can be identified using imaging techniques such Doppler ultrasonography and greyscale ultrasound.